Pan-Cancer Analysis Shows TP53 Mutations Modulate the Association of NOX4 with Genetic Programs of Cancer Progression and Clinical Outcome - Wei Feng Ma; Howard E. Boudreau; Thomas L. Leto (MDPI AG, 2021)
Previously, we have shown TGF-β-induced NOX4 expression is involved in the epithelial-to-mesenchymal transition (EMT), a process critical for cancer metastasis, and that wild-type (WT) and mutant (Mut) p53 have divergent effects on TGF-β induction of NOX4: WT-p53 suppresses whereas Mut-p53 augments NOX4 mRNA and protein production in several tumor cell models. We sought to validate and extend our model by analyzing whole-exome data of primary tumor samples in The Cancer Genome Atlas (TCGA). We constructed a Pan-Cancer dataset from 23 tumor types and explored NOX4 expression patterns in relation to EMT and patient survival. NOX4 mRNA levels increase as a function of cancer progression in several cancers and correlate with Mut-p53 mRNA and genes involved in programs of EMT, cellular adhesion, migration, and angiogenesis. Tumor macrophages appear to be a source of NOX2, whose association with genetic programs of cancer progression emulate that of NOX4. Notably, increased NOX4 expression is linked to poorer survival in patients with Mut-TP53, but better survival in patients with WT-TP53. NOX4 is negatively associated with markers of apoptosis and positively with markers of proliferation in patients with Mut-TP53, consistent with their poorer survival. These findings suggest that TP53 mutations could "switch" NOX4 from being protective and an indicator of good prognosis to deleterious by promoting programs favoring cancer progression.